2010
DOI: 10.1073/pnas.0909380107
|View full text |Cite
|
Sign up to set email alerts
|

DNA as a universal substrate for chemical kinetics

Abstract: Molecular programming aims to systematically engineer molecular and chemical systems of autonomous function and ever-increasing complexity. A key goal is to develop embedded control circuitry within a chemical system to direct molecular events. Here we show that systems of DNA molecules can be constructed that closely approximate the dynamic behavior of arbitrary systems of coupled chemical reactions. By using strand displacement reactions as a primitive, we construct reaction cascades with effectively unimole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
484
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(489 citation statements)
references
References 46 publications
3
484
0
2
Order By: Relevance
“…The same condition holds for P T and P A , which are used to produce T and A respectively, so these species are also modelled as having constant concentrations. In vivo, the stability of precursor concentrations could be achieved through buffering [19], whereas in vitro, high concentrations of these precursors could cause them to remain effectively constant over long time periods [9,20].…”
Section: Comparator Designmentioning
confidence: 99%
“…The same condition holds for P T and P A , which are used to produce T and A respectively, so these species are also modelled as having constant concentrations. In vivo, the stability of precursor concentrations could be achieved through buffering [19], whereas in vitro, high concentrations of these precursors could cause them to remain effectively constant over long time periods [9,20].…”
Section: Comparator Designmentioning
confidence: 99%
“…It has been shown that such arbitrary systems of chemical reactions can be faithfully implemented in a biochemical setting by compiling them into an enlarged system of DNA strand displacement reactions [50]. By contrast, our design is influenced by more practical considerations and is targeted to a specific implementation framework using DNAzymes.…”
Section: Related Workmentioning
confidence: 99%
“…Note that while we have found numerically conditions in which a WTA effect occurs in DNA-only circuits, it is not guaranteed that a unique winner will exist whenever competition for fuel occurs. Strand displacement is prone to leak, which is thought to arise mainly from blunt-end displacement (displacement of a strand from a duplex without the assistance of a toehold) [32,65,66]. Leak is especially problematic for first-order rsif.royalsocietypublishing.org J R Soc Interface 10: 20130212 autocatalytic circuits because they amplify exponentially even a miniscule leak (contrary to second-order amplification which occurs only above a threshold, in the presence of first-order degradation) [31].…”
Section: ð1:8þmentioning
confidence: 99%